Pushover analysis of the reinforced concrete frames with soft first storey using a fiber hinge model - Abdesslam, Issam; Mellas, Mekki (Journal of Applied Engineering Science & Technology, 2018)
In seismic zones, the problem with the soft storey is amongst the factors that causes the formation of the rupture mechanism in reinforced concrete structures due to variation in the lateral stiffness between levels. Most seismic codes have addressed this phenomenon in realizing the admissible lateral stiffness ratio between levels, without specifying the method to be used in determining this stiffness. The current study is aiming at determining the secant stiffness of each level by using the level capacity curve obtained by nonlinear static pushover analysis, based on a fiber hinge model. The results obtained made it possible to plot a curve that represents the variation of the elastic or secant stiffness ratio between the first level and the second level of a construction as a function of a displacement at the top of the structure. This curve examines the possibility of occurrence of a first soft storey for different points of performance.